Intravenous Peramivir for Treatment of Influenza in Hospitalized Patients. Issue 4 (May 2014) - Ison, Michael G; Fraiz, Joseph; Heller, Barry; Jauregui, Luis; Mills, Graham; O'Riordan, William; O'Neil, Brian; Playford, E Geoffrey; Rolf, J Douglass; Sada-Diaz, Eduardo; Elder, Jenna; Collis, Phil; et al.
Background: Influenza causes over 200, 000 hospitalizations a year in the United States, but few antiviral treatment studies have focused on patients hospitalized with influenza. This open-label, randomized study was initiated during the 2009 H1N1 pandemic to help assess the antiviral activity, safety and tolerability of 5–10 days treatment with two different dosing regimens of the intravenous neuraminidase inhibitor, peramivir, in hospitalized subjects with influenza. Methods: Quantitative virology was done on nasopharyngeal swab specimens from subjects ≥6 years of age to measure change from baseline in tissue culture infective dose (primary end point) and quantitative viral RNA levels by real-time PCR. Clinical end points included time to clinical resolution, a composite end point of four vital signs and oxygen saturation. Results: A total of 234 hospitalized patients were randomized to peramivir 300 mg twice daily or 600 mg once daily; 127 had laboratory confirmed influenza. In those with detectable virus at baseline, viral titres declined without differences between regimens. There were no significant differences in clinical or virological end points between treatment arms, and apparent differences were explained by baseline disease severity differences in the groups. Peramivir was generally safe and well tolerated for treated patients hospitalized with pandemic influenza with outcomes similar to those described in the literature. Conclusions: This open-label trial of intravenous peramivir in subjects hospitalized predominantly with 2009 influenza A (H1N1) demonstrated that once- or twice-daily administration was associated with decreases in viral shedding and clinical improvement. ClinicalTrials.gov number NCT00957996.